Quantitative phase separation in multiferroic Bi0.88Sm0.12FeO3 ceramics via piezoresponse force microscopy - Alikin, D. O. (2017)
BiFeO3 (BFO) is a classical multiferroic material with both ferroelectric and magnetic ordering at room temperature. Doping of this material with rare-earth oxides was found to be an efficient way to enhance the otherwise low piezoelectric response of unmodified BFO ceramics. In this work, we studied two types of bulk Sm-modified BFO ceramics with compositions close to the morphotropic phase boundary (MPB) prepared by different solid-state processing methods. In both samples, coexistence of polar R3c and antipolar P-bam phases was detected by conventional X-ray diffraction (XRD); the non-polar P-nma or P-bnm phase also has potential to be present due to the compositional proximity to the polar-to-non-polar phase boundary. Two approaches to separate the phases based on the piezoresponse force microscopy measurements have been proposed. The obtained fractions of the polar and non-polar/anti-polar phases were close to those determined by quantitative XRD analysis. The results thus reveal a useful method for quantitative determination of the phase composition in multi-phase ceramic systems, including the technologically most important MPB systems. (C) 2015 AIP Publishing LLC.